Digital Transformation of MSMEs in Timor Leste: A Conceptual Study of the Role of Technology Adoption, Government Support, and Digital Training on Competitiveness - das Neves, Cipriano Bruno; Soares, Casimiro; Ceu Fatima, Arlindo de; Araujo Tilman, Adolfo de; Gusmão, Leocadia Soares; da Costa, Caetano (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2025)
MSMEs in Timor-Leste play a crucial role in driving national economic growth, yet they still face significant challenges in enhancing their competitiveness in the digital era. This conceptual study aims to outline the role of information technology adoption, government support, and digital training in driving MSME digital transformation. This study employs a literature review approach combined with primary data collection, reviewing various academic sources, policy reports, relevant previous research findings, and conducting field research with local MSMEs. Through descriptive-analytical analysis, the study identifies that technology adoption can accelerate business efficiency and innovation, government support serves as a catalyst through regulations, incentives, and infrastructure, while digital training contributes to increasing human resource capacity. These three factors complement each other and have the potential to strengthen MSME competitiveness both locally and globally. This study emphasizes that digital transformation is not only a requirement but also a crucial strategy for the sustainability of MSMEs in Timor-Leste. Therefore, the results of this study can serve as a basis for policy formulation, business strategies, and further research related to strengthening MSMEs in facing the challenges of digitalization.